2012
DOI: 10.4322/apa.2014.087
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of the Diesel-Contaminated Soil of the Brazilian Antarctic Station

Abstract: Antarctic soils are under constant risks of oil contamination due the presence of scienti c stations. Bioremediation is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Many natural terrestrial and aquatic environments (e.g., deserts, polar regions, geothermal environments, supersaturated salt pools, acidic or soda lakes, and the deep sea) were originally thought to be too harsh to harbor life (Carré et al, 2022). However, more recent studies have demonstrated the occurrence of a wide diversity of organisms in these extreme habitats (Jurelevicius et al, 2012;Cury et al, 2015;Lopez et al, 2019;Shu and Huang, 2022). Microorganisms able to tolerate, survive, or require extreme conditions to grow optimally are known as extremophiles (Brock and Freeze, 1969;MacElroy, 1974;Rothschild and Mancinelli, 2001), whereas those that grow optimally under multiple extreme stress conditions are known as polyextremophiles (Capece et al, 2013).…”
Section: Bioprospecting the Metabolic Potential Of Cultured Extremoph...mentioning
confidence: 99%
“…Many natural terrestrial and aquatic environments (e.g., deserts, polar regions, geothermal environments, supersaturated salt pools, acidic or soda lakes, and the deep sea) were originally thought to be too harsh to harbor life (Carré et al, 2022). However, more recent studies have demonstrated the occurrence of a wide diversity of organisms in these extreme habitats (Jurelevicius et al, 2012;Cury et al, 2015;Lopez et al, 2019;Shu and Huang, 2022). Microorganisms able to tolerate, survive, or require extreme conditions to grow optimally are known as extremophiles (Brock and Freeze, 1969;MacElroy, 1974;Rothschild and Mancinelli, 2001), whereas those that grow optimally under multiple extreme stress conditions are known as polyextremophiles (Capece et al, 2013).…”
Section: Bioprospecting the Metabolic Potential Of Cultured Extremoph...mentioning
confidence: 99%
“…Rubbish dumps of these abandoned stations, for example, continue to leach chemicals and traces of heavy metals into the surrounding ice‐free areas (Deprez et al ) and warming temperatures will likely accelerate this damage (CEP ). Increased human activity also brings the risk of damage to the environment, particularly from fuel spills (Cury et al ), and the introduction of invasive species (Vidas ).…”
Section: Introductionmentioning
confidence: 99%